Local Wisdom of the Martumba Tradition of the Toba Batak Community in Sianjur Mula-Mula Village, Samosir Regency, North Sumatra: Anthropolinguistic Study - Irma Yuli Aritonang; Robert Sibarani; Alemina Br Perangin-Angin (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to describe local wisdom in the martumba tradition in the Toba Batak community in Sianjur Mula-Mula Village, Sianjur Mula-Mula District, Samosir Regency, North Sumatra Province. Local wisdom in the martumba tradition can be seen in every tumba in that tradition. Local wisdom is a cultural heritage that is always present in a tradition and can be preserved to be passed down from generation to generation. The method used in this tradition is the qualitative method. The data used in this study is the local wisdom that exists in this tradition. The results of this study are that there are five (5) local wisdoms in the Martumba tradition, namely social solidarity and mutual cooperation, kinship, mutual respect, gratitude and cultural preservation.